Gastrointestinal Endoscopy in the Era of COVID-19 - Perisetti, Abhilash; Goyal, Hemant; Sharma, Neil (Frontiers in Medicine, 2020)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which led to a worldwide pandemic started in early 2020. Healthcare systems across the world encountered an unprecedented surge of COVID-19 patients resulting in more than half a million deaths globally. COVID-19 has affected multiple sub-specialties and procedure-related fields, including gastroenterology. Gastrointestinal (GI) endoscopy centers are specialized units where thousands of endoscopies are performed annually. A significant proportion of these procedures are affected due to the national and regional lockdowns across the globe. To adapt to this rapidly evolving situation, endoscopy centers have undergone significant changes and have taken unprecedented precautions to avoid the transmission of the virus. However, endoscopy centers are going through financial strain due to a reduction in the number of procedures from lockdowns and fear of virus transmission. Theoretically, endoscopies could add to the disease transmission as SARS-CoV-2 has shown to be present in the GI secretions. Multiple precautions such as mandatory use of face-masks, safe distancing, use of barriers between the endoscopists and patients, negative pressure rooms, extended use of personal protective equipment, and volume reduction have been taken to decrease the risk of disease transmission by these centers. Moreover, pre-endoscopy COVID-19 testing has now become a norm. In this review, we highlight the significant changes assumed by the endoscopy center. Furthermore, we discuss cost-related concerns of pre-endoscopy COVID-19 testing, the downtime, and delays related to the procedures, and effects of rescheduling. As the pandemic progresses through multiple phases, endoscopy centers should use a dynamic approach to adapt and strive to provide the best patient care.